Pengembangan Media Pembelajaran Interaktif Berbentuk Video Animasi Berbantuan Aplikasi Filmora Pada Pembelajaran Pecahan Siswa Kelas V Sekolah Dasar - Ditha Tiara; Sutarini (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to analyze student responses, validity and effectiveness of the development of interactive learning media in the form of animated videos assisted by Filmora application in learning fractions of grade V elementary school students. This research uses the learning device development model suggested by S.Thiagarajan, namely the 4d model (Define, Design, Develop and Disseminate). The instruments used in this research are validation questionnaire, needs and test sheets. From the results of student responses, it is known that students really like and are interested in interactive learning media in the form of animated videos aided by the Filmora application that researchers develop, it can be seen from the student response which shows an average of 83.5% with the criteria